The Case of Alpenrind - Schöffmann, Peter C. (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2020)
The Alpenrind case (C-527/16) revealed opposing positions between the Member States providing services feely across Europe and the Member States fearing for social dumping. A tension the Union is grappling with for a certain time, and that increased in the last years. Many (mostly western) Member States believe that the posting of workers is undermining their social standards and hampering their labour markets. They are not convinced that Union law provides an adequate level to prevent abusive practices. Therefore, these Member States try to take countermeasures by implementing restrictive legislation: imposing obligations on employers to provide documents and comply with notification requirements. This leads to an additional burden potentially impeding the freedom of movement of workers and services; an effect the Social Coordination Regulations actually intend to prevent. The Alpenrind case deals with two questions regarding the postal rule`s impact on social security coordination. It addresses the condition of non-replacement as well as the binding effect of Portable Document A1. However, set in a broader context, it reveals the inherent contradiction of social security coordination. The Union finds itself having to strike a balance between the freedom to provide services and the protection against social dumping.